Nitrogen and phosphorus recovery from hemodialysis wastewater to use as an agricultural fertilizer - Faissal Tarrass; Hamza Benjelloun; Meryem Benjelloun (Nefrología, 2023)
Introduction: Hemodialysis wastewater contains high concentrations of ammonia nitrogen and phosphorus. Recovery of these nutrients as soil fertilizers represents an interesting opportunity to ensure a sustainable fertilizer supply. Methods: In this paper, a simple method for recovering phosphorous and nitrogen as crystalline struvite [MgNH4PO4·6H2O] is presented. An integrated cost model is also presented in order to create a positive business case. Results: Recovery rates in form of struvite of 95% of PO43−-P and 23% of NH4+-N were achieved with a profit. Conclusion: To the best of our knowledge, this paper is the first to study the recovery of these naturally occurring minerals from hemodialysis wastewater. This offers great potential for the valorization of this type of wastewater. Resumen: Introducción: El agua residual de la hemodiálisis contiene altas concentraciones de nitrógeno amoniacal y fósforo. La recuperación de dichos nutrientes como fertilizantes del suelo representa una oportunidad interesante para garantizar un suministro de fertilizantes sostenible. Métodos: En este documento se presenta un método simple de recuperar fósforo y nitrógeno en forma de cristales de estruvita [MgNH4PO4·6H2O]. También se presenta un modelo de costes integrado para crear un caso de negocio positivo. Resultados: Se lograron unas tasas de recuperación en forma de estruvita del 95% de PO4 3−-P y el 23% de NH4 +-N, con beneficio. Conclusión: Según nuestros conocimientos, este documento es el primero que estudia la recuperación de estos minerales de origen natural del agua residual de la hemodiálisis, lo cual ofrece un gran potencial para la valorización de este tipo de aguas residuales.